Hubungan Penyakit Jantung pada Kehamilan dengan Kematian Maternal di RSUD Abdul Moeloek Bandar Lampung periode 2016—2019 - Regina Pingkan; Ratna Dewi Puspita Sari; Diana Mayasari; Taufiqurrahman Rahim (MAJORITY, 2022)
Maternal mortality is maternal deaths during pregnancy, childbirth, and puerperium but not due to other causes such as accidents or falling in every 100,000 live births. One of the important risk factors for maternal mortality is Peripartum Heart Disease. Peripartum Heart Disease (PPHD) is the highest cause of maternal death in 2018 at Abdul Moeloek Hospital in Bandar Lampung. This study aims to determine the relation between PPHD and maternal mortality. This research was a retrospective cohort study design and conducted in October—November 2019 at Abdul Moeloek Hospital in Bandar Lampung. The research sample was 96 respondents obtained using simple random sampling technique. The data used are secondary data from medical records from January 2016 to September 2019. The case group consisted of 48 pregnant women suffering from cardiac disease and the control group consisted of 48 pregnant women who did not suffer from cardiac disease. Data were analyzed by univariate and bivariate tests using the chi-square statistical test with α = 0.05.There were 9 respondents (18.75%) in the case group who experienced maternal death and 1 respondent (2.1%) in the control group who experienced maternal death. Statistical test results obtained there is a relation between Peripartum Heart Disease with maternal mortality in RSUD Abdul Moeloek Bandar Lampung period of 2016—2019.